Efektivitas Kombinasi Amelioran dan Pupuk Kandang dalam Meningkatkan Hasil Kedelai pada Tanah Ultisol - Sudaryono, Sudaryono; Wijanarko, Andy; Suyamto, Suyamto (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
Major constraint in soybean production on Ultisol soil includes: high soil acidity, veryhigh Al and Fe level, low organic matter, nutrient deficiency, low of base saturation and cation exchange capacity (CEC). This study was aimed at finding an optimal dose and combination of organic manure and soil ameliorants to achieve high yield of soybean in Ultisol soil in Lampung. The experiment was conducted in a greenhouse of the Indonesian Legumes and Tuber Crops Research Institute (ILETRI), Malang, East Java, and on a dry land of Rumbia district, Lampung Tengah, in the 2005 growing season. Four series of experiments were conducted in the greenhouse using four different ameliorants (dolomite, zeolite, limestone, and organic ameliorant Formula 1). The glasshouse trial was arranged in a completely randomized design with two factors and four replications. The first factor consisted of five ameliorant levels, namely 0, 150, 300, 450, and 600 kg/ha. The second factor consisted of four manure levels, namely 0, 500, 100, and 1500 kg/ha. In the field experiment, a randomized complete block design was used with four replications. Two ameliorants, dolomite and zeolite, were used and the treatment combinations were the same as those in the glasshouse trial. Results indicated that ameliorant zeolite, dolomite, limestone, and Formula 1 increased plant height, seed weight (yield/pot), and yield of soybean in the field. The effective dose of ameliorant application to achieve 2.0-2.5 t/ha soybean yield was a combination of 500-100 kg/ha manure and 150-450 kg/ha each one of the ameliorants dolomite, zeolite, lime or Formula 1. An effective way to apply the soil ameliorant was by placing it in the planting hole or by distributing it along the plant rows. The use of ameliorant in the form of organic Formula 1 can be reduced down to 2,500 kg/ha. The need of ameliorant in the form of natural mineral (dolomite, zeolite, limestone) can be reduced down to 1,500 kg/ha. Combinations of ameliorant with organic manure showed increase of the effectiveness of the amelioration on Ultisol soil. The optimum combination of soil ameliorant and organic manure was 500 to 1,000 kg/ha organic manure and 150 to 450 kg/ha ameliorant.